PROGRAMAS DE SUPLEMENTAÇÃO ALIMENTAR COM LEITE E A AGENDA DE SEGURANÇA ALIMENTAR E NUTRICIONAL BRASILEIRA - André Teixeira Vessoni; Patricia Constante Jaime (Universidade do Estado do Rio de Janeiro, 2019)
The aim of the current study is to describe milk supplementary feeding programs held in Brazilian states and capitals, as well as to discuss their pertinence and compliance with the national food and nutrition security agenda. Methods: the current programs were mapped (through government websites) and described (through electronic forms sent to public administration bodies). Reflections about the herein described programs were based on the II National Food and Nutrition Security Plan and on the National Food and Nutrition Policy. Results: In total, 14 state and 5 municipal programs were mapped. Six (6) programs were described, in total: 4 state programs (PAA-Leite in Minas Gerais and Pernambuco; VivaLeite in São Paulo; Provimento Alimentar Institucional in the Federal District) and 2 municipal programs (Leve Leite in São Paulo; Leite do Meu Filho in Manaus). These programs were evaluated based on the use of social registry databases for planning and monitoring purposes; on the convergence towards public polices focused on family farming; and on the convergence towards the agenda for the promotion of adequate and health eating among children younger than 2 years. Conclusions: PAA-Leite and Provimento Alimentar Institucional are the closest programs to the assumptions and challenges set by the food and nutrition security agenda. VivaLeite, Leve Leite and Leite do Meu Filho are the farthest programs from this agenda. DOI:10.12957/demetra.2019.37229